(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
ITO (indium-tin-oxide) is used widely as the anode electrode in organic electroluminescence devices (OLEDs). Several studies have dealt with the effect of ITO chemical treatment but to the OLEDs performance have not been considered the effect of this treatment. We were present here results regarding these effect.We studies of the effect of surface treatments on the properties of ITO substrate. We were performed chemical treatment with RCA and Aqua regiaof the OELDs. Since we will understand the properties of OELDs, we were performed Fowler-Nordheim tunneling. The buffer layer and ITO surface treatment were performed to increase the efficiency of the OLEDs. As a result, we were obtained conform the surface properties of ITO can be significantly changed by chemical treatment. The oxygen decrease produced by chemical treatment lead to increase of oxygen vacancies. We conformed that the oxygen vacancies role on increasing carrier injection. A study on the cause of improving the performance of the device using the surface treatment and the usingthe buffer layer will be of great help in understanding the relationship between the properties of the ITO substrate and the organic electroluminescent device.